Neurological improvement following revision of vascular graft remnants in the upper extremity - Marie Bigot, BS; Sima Vazquez, MS; Sateesh Babu, MD; Suguru Ohira, MD; Ramin Malekan, MD; Igor Laskowski, MD; Jared Pisapia, MD, MSTR (Journal of Vascular Surgery Cases and Innovative Techniques, 2024)
Remnant vascular grafts may result in significant neurological deficits owing to compression of adjacent neural structures. We report this finding in two cases after extracorporeal membrane oxygenation decannulation and removal of an arteriovenous fistula in the upper extremity. In both cases, removal of the graft, patch arteriotomy, and external neurolysis resulted in significant recovery of neurological function. We review the preoperative workup, diagnostic studies, and technical approach to treatment in an effort to increase recognition among vascular and cardiovascular surgeons and to demonstrate a safe and effective management option through a multidisciplinary approach.